Nocturnal antihypertensive treatment in patients with type 1 diabetes with autonomic neuropathy and non-dipping of blood pressure during night time: protocol for a randomised, placebo-controlled, double-blind, two-way crossover study. Issue 10 (7th October 2014) - Hjortkær, Henrik; Jensen, Tonny; Kofoed, Klaus; Mogensen, Ulrik; Køber, Lars; Hilsted, Karen Lisa; Corinth, Helle; Theilade, Simone; Hilsted, Jannik
Abstract : Introduction: Cardiac autonomic neuropathy (CAN) and elevated nocturnal blood pressure are independent risk factors for cardiovascular disease in patients with diabetes. Previously, associations between CAN, non-dipping of nocturnal blood pressure and coronary artery calcification have been demonstrated. The present protocol describes a trial to test the efficacy of bedtime dosing of the ACE inhibitor enalapril on night time blood pressure and left ventricular mass in patients with type 1 diabetes. Materials and methods: In a randomised, double-blind, two-way cross-over study, 24 normoalbuminuric patients with type 1 diabetes with CAN will be treated for 12 weeks with either morning or bedtime dosing of 20 mg enalapril, followed by 12 weeks of switched treatment regimen. During each treatment period, two 24 h ambulatory blood pressure measurements will be performed and after each treatment period left ventricular mass will be determined by multisliced CT. Primary end points will be reduction in blood pressure and reduction in left ventricular mass. Ethics and dissemination: The study has been approved by the Danish Medicines Agency, the Scientific-Ethical Committee of the Capital Region of Denmark and the Danish Data Protection Agency. An external monitoring committee (the Good Clinical Practice Unit at Copenhagen University Hospital) will oversee the study. The results of the study will be presented at national and international scientific meetings and publications will be submitted to peer-reviewed journals. Trial registration number: EudraCT (2012- 002136-90).